VEGETATIVE DYSFUNCTION AND REPOLARIZATION DISORDERS ON RESTING ECG AND IN EXERTION IN YOUNGER PERSONS WITH MARFANOID PHENOTYPE AND MITRAL VALVE PROLAPSE - S. V. Reeva; E. G. Malev; E. F. Timofeev; I. A. Pankova; B. I. Zaripov; T. I. Belousova; E. V. Zemtsovsky (Российский кардиологический журнал, 2015)
Aim. To estimate the prevalence of disordered repolarization and its relation with the character of vegetative dysfunction in younger persons with MP and MVP.Material and methods. Totally 285 persons studied of the young age (mean age 19,4+1,4 y.). Phenotypical, anthropometric and clinical investigation performed, ECG, EchoCG, Holter monitoring (HM) of ECG and BP, treadmill test. The heart rate variability (HRV) was assessed, cardiovascular tests performed.Results. MP and MVP are the most common dysplastic phenotypes in younger persons and have 15% ad 10% prevalence, respectively. The analysis of the treadmill test results, done for 140 of participants (80 males) showed that the youths studied had good tolerance of physical exertion (PET at the average or high level). In men with MVP and MP comparing to almost healthy individuals there was tendency to the decrease of PET and slowed down recovery of BP and pulse rate, that witnesses the decrease of adaptation abilities in the assessed persons of those groups. Disordered repolarization on resting ECG and during exercise test was found in MVP and MP, as in controls. However, the prevalence of T inversion during exercise test in MVP and MP was much higher, than in controls. HRV and vegetative tests analysis did not reveal significant differences in vegetative regulation in persons with EVRS on resting ECG and in the group of DR with PE.